Commerce and culture in the Bay of Bengal, 1500-1800 - Prakash, Om, 1940-; Lombard, Denys; Indian Council of Historical Research; Indo-French Seminar on "the Bay of Bengal in the Asian Maritime Trade and Cultural Network, 1500-1800" (1994 : New Delhi, India) (New Delhi : Manohar, 1999)
Collection of essays presented at an Indo-French Seminar on "the Bay of Bengal in the Asian Maritime Trade and Cultural Network, 1500-1800" held in New Delhi in December 1994.
Includes bibliographical references and index.
Keywords: India -- Commerce -- History -- Congresses; Bengal, Bay of -- Commerce -- History -- Congresses